Effects of different conductive ions on pore-structure evolution of medium- and high-rank coal bodies induced by electric pulses. (1st June 2021) - Wang, Yihan; Yang, Wei; Lin, Baiquan; Yan, Fazhi
Highlights: The change law of different conductive ions adsorbed by coal was studied to improve the conductivity of coal. The variation law of breakdown strength of coal samples was studied, so as to improve the safety and efficiency of pulsatted coal. The change characteristics of fracture structure in medium - and high - rank coal body was studied to promote gas permeability and desorption. Abstract: Electric pulse fracturing technology is a new type of coal seam fracturing and permeability increasing technology based on high-pressure shock wave technology. Compared with conventional technology, electric pulse fracturing has the advantages of a higher energy efficiency, less environmental pollution, and a shorter fracturing time, but having the disadvantages of rapid energy loss and a small fracture radius. To reduce the energy loss of electric pulses and increase the fracture radius, the experimental system of high-voltage electric pulse was employed in this study. The effects of NaCl, CaCl2, and AlCl3 conductive ions on the evolution of the pore structure induced by electric pulses were examined for medium- and high-rank coal bodies. The experimental results indicated the adsorption capacity of coal for ions was positively correlated with the valence of the cations and the soaking time, and the amount of ions adsorbed was larger when the solution was more alkaline. Amounts of ions adsorbed onto the coal surface decreased in the following order Al 3+ > Ca 2+ > Na + . After the treatment, the conductivity of the coal was significantly improved, making the plasma channel in the coal body more fully developed in the process of high-voltage electric pulse impaction, thus reducing significantly the breakdown voltage of the coal samples. Additionally, tthe total pore volume, total specific surface area, porosity, and average pore diameter of the treated coal increased and that the percentages of macropores and mesopores increased, indicating that the pore structure of coal samples is significantly improved.